A Note on the Numerical Modelling of Viscoplastic Damage - P. Kłosowski; R. Schmidt; D. Weichert (Engineering Transactions, 2015)
In this paper, a numerical model of the viscoplastic behaviour of metals including damage effects is proposed. The Chaboche model of constitutive equations accounting for viscoplasticity coupled to damage is applied. Three types of uniaxial tests are presented: constant strain rate tests, creep tests, and cyclic loading tests. Numerical results for rupture under cyclic loading are compared to experimental results given in [1]. Results of calculations based on pure viscoplastic material behaviour are compared to those including damage effects. The present investigations are preliminary to the implementation of the proposed model into more general FEM codes.